Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1088/0031-9155/54/14/010
|View full text |Cite
|
Sign up to set email alerts
|

Introducing DeBRa: a detailed breast model for radiological studies

Abstract: Currently, x-ray mammography is the method of choice in breast cancer screening programmes. As the mammography technology moves from 2D imaging modalities to 3D, conventional computational phantoms do not have sufficient detail to support the studies of these advanced imaging systems. Studies of these 3D imaging systems call for a realistic and sophisticated computational model of the breast. DeBRa (Detailed Breast model for Radiological studies) is the most advanced, detailed, 3D computational model of the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…These simulation methods can be divided into two major categories: (i) methods based upon rules for generating anatomical structures in the breast [1][2][3][4][5][6][7][8] and (ii) methods based upon individual clinical 3D breast images. [9][10][11] These two categories of methods are complementary; while the second category offers an increased level of realism due to the use of clinical data, the first category offers more flexibility to cover clinically observed variations in breast anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…These simulation methods can be divided into two major categories: (i) methods based upon rules for generating anatomical structures in the breast [1][2][3][4][5][6][7][8] and (ii) methods based upon individual clinical 3D breast images. [9][10][11] These two categories of methods are complementary; while the second category offers an increased level of realism due to the use of clinical data, the first category offers more flexibility to cover clinically observed variations in breast anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…2 Power-law backgrounds have been widely used as a statistical model for breast backgrounds, [3][4][5][6][7][8][9] and power-law exponents in clinical tomosynthesis and breast CT images have been investigated. 10,11 To date, power-law coefficients have been estimated from the radial averaged of the power spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue compositions are usually taken from Hammerstein et al 13 More complex phantoms can be generated by simulating 3D breast tissue distribution, obtained by applying the concept of 3D power law noise. 14,15 Advanced breast models with 3D realistic breast tissue distribution and anatomical features [16][17][18] have been developed in order to carry out feasibility studies with 2D and 3D x-ray breast imaging techniques, including optimization of image number and dose per image in digital breast tomosynthesis and breast dual energy, 10,15,[18][19][20] as well as to perform accurate breast dosimetry, 21 evaluate nonrigid mammogram registration techniques, 22 calculate the properties of the digital mammograms 23 and investigate the effect of digital breast tomosynthesis acquisition parameters on computer-extracted texture features. 24,25 These models offer complex breast tissue simulation and allow the generation of realistic synthetic mammograms which resemble the real ones.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 These models offer complex breast tissue simulation and allow the generation of realistic synthetic mammograms which resemble the real ones. Recently, Ma et al 18 reported an advanced new breast model suitable for work with general purpose Monte Carlo codes for simulation of x-ray projection images. Synthetic mammograms are calculated utilizing basically two approaches.…”
Section: Introductionmentioning
confidence: 99%